The Influence of Work Conflict and Work Stress on Employee Performance at PT SEN, Jak-Bar - Arianto, Nurmin; Mildova, Ega (Universitas Pamulang, 2024)
The aim of this research is to determine the effect of work conflict and work Stress on employee performance using data collection methods using closed questionnaires and data analysis techniques using multiple regression analysis and hypothesis testing. The number of samples in this research is 70 respondents. From the results of distributing questionnaires, it is known that work conflict has no influence on performance and work Stress has an influence, while together conflict and work Stress have an influence on employee performance.